A tree-ring based precipitation reconstruction for the Mohe region in the northern Greater Higgnan Mountains, China, since AD 1724. Issue 1 (July 2014) - Zhang, Tongwen; Yuan, Yujiang; Wei, Wenshou; Yu, Shulong; Zhang, Ruibo; Chen, Feng; Shang, Huaming; Qin, Li
Abstract: August–July precipitation has been reconstructed back to AD 1724 for the Mohe region in the northern Greater Higgnan Mountains, China, using Pinus sylvestris var. mongolica tree-ring width. The reconstruction explains 39% of the variance in the precipitation observed from AD 1960–2008. Some droughts noted in historical documents are precisely captured in our reconstruction. Wet periods occurred during the periods of AD 1734–1785, AD 1805–1830, AD 1863–1880, AD 1922–1961, and AD 1983–1998; while the periods of AD 1786–1804, AD 1831–1862, AD 1881–1921, and AD 1962–1982 were relatively dry. Power spectral and wavelet analyses demonstrated the existence of significant 24-yr, 12-yr, and 2-yr cycles of variability. The results of the spatial correlations suggest that our reconstruction contains climatic signals for the southern Stanovoy Range and the northern Greater Higgnan Mountains. The positive correlations between the new reconstructed precipitation series and two precipitation reconstructions indicate that our precipitation reconstruction captures broad-scale regional climatic variations. A comparison between the weakening tendency of summer monsoon and the dry period of our reconstruction reveals that the annual precipitation in the Mohe region is partly influenced by the East Asian Summer Monsoon.